Start-up flow in shallow deformable microchannels. (25th February 2020) - Martínez-Calvo, Alejandro; Sevilla, Alejandro; Peng, Gunnar G.; Stone, Howard A.
Abstract : Abstract : Microfluidic systems are usually fabricated with soft materials that deform due to the fluid stresses. Recent experimental and theoretical studies on the steady flow in shallow deformable microchannels have shown that the flow rate is a nonlinear function of the pressure drop due to the deformation of the upper soft wall. Here, we extend the steady theory of Christov et al. ( J. Fluid Mech., vol. 841, 2018, pp. 267–286) by considering the start-up flow from rest, both in pressure-controlled and in flow-rate-controlled configurations. The characteristic scales and relevant parameters governing the transient flow are first identified, followed by the development of an unsteady lubrication theory assuming that the inertia of the fluid is negligible, and that the upper wall can be modelled as an elastic plate under pure bending satisfying the Kirchhoff–Love equation. The model is governed by two non-geometrical dimensionless numbers: a compliance parameter $\unicode[STIX]{x1D6FD}$, which compares the characteristic displacement of the upper wall with the undeformed channel height, and a parameter $\unicode[STIX]{x1D6FE}$ that compares the inertia of the solid with its flexural rigidity. In the limit of negligible solid inertia, $\unicode[STIX]{x1D6FE}→ 0$, a quasi-steady model is developed, whereby the fluid pressure satisfies a nonlinear diffusion equation, with $\unicode[STIX]{x1D6FD}$ as the only parameter, which admits a self-similar solution under pressure-controlled conditions. This simplified lubrication description is validated with coupled three-dimensional numerical simulations of the Navier equations for the elastic solid and the Navier–Stokes equations for the fluid. The agreement is very good when the hypotheses behind the model are satisfied. Unexpectedly, we find fair agreement even in cases where the solid and liquid inertia cannot be neglected.